Social Skills and Sensory Processing in Preschool Children Who are Homeless or Poor Housed. Issue 2 (3rd April 2019) - Rybski, Debra; Israel, Heidi
ABSTRACT: Social skills and sensory processing were examined in 91 homeless or poor housed preschool children. The Social Skills Rating Scale measured children's social skills/behavior problems and the Short Sensory Profile measured sensory and behavioral responses. Children who were poor housed had better social skills, fewer problem behaviors and better sensory processing than homeless children. Social skill/problem behaviors and sensory processing concerns were positively correlated in both groups of children. This insight into homeless and poor housed children's social/behavioral and sensory processing supports a model for early identification and intervention to enhance children's development, occupational performance, social participation and learning.